Obstructive sleep apnea in relation to orthodontic treatment in children - Z. Vranková; P. Turčáni; P. Horník; A. Bryšová; L. Izakovičová Hollá; P. Černochová; P. Bořilová Linhartová (Czech Dental Chamber, 2020)
Introduction, aim: Obstructive Sleep Apnea (OSA) is defined as the collapse of the upper respiratory tract, complete or partial, leading to hypopnea to apnea. This collapse is repeated several times during the night. As this sleep-related breathing disorder (SRBD) manifests itself differently in adults and in children, there is also a separate diagnosis of OSA occuring in childhood. For most children, we can see loud night snoring, mouth breathing, disturbed sleep continuity and its architecture, and therefore OSA has an impact not only on the physical but also on the child's mental health and development. Correct diagnosis, in the most precise way with polysomnography and subsequent selection of therapy should be done as soon as possible. The risk factors for OSA in children include obesity, adenotonsillar hypertrophy, neuromuscular diseases or craniofacial malformations. The aim of the review article is to outline the relationship between OSA and orthodontic anomalies in children and to summarize current trends in their therapy.Cephalometric studies in pediatric patients with OSA indicate that there are several craniofacial features that can interfere with upper respiratory tract patency and contribute to the onset or aggravation of this disorder. These include, for example, a vertical growth pattern and increased basal bones divergence, often visible on the frontal open bite and the lack of the lip seal. In patients, we often describe a second skeletal class with increased overjet, the jaws may be in retrognathic position, and the anterio-posterior dimension of the bony portion of the nasopharynx is therefore affected and reduced. The micrognathism or microgenia, narrowed nasomaxillary complex, high and narrow palate, often manifested by lateral crossbite, is also increasing the risk of OSA. The effect of agenesis or early tooth loss is being examined.An imbalance in the development of orofacial structures in early childhood can lead to a disruption of the normal development of the bony support of the upper respiratory tract and therefore cause an increased risk of the development of SRBD. Conclusion: Properly timed orthodontic treatment for children with dysmorphism leading to narrowed upper respiratory tract can stimulate the growth of the jaws, improving their proper development while reducing the risk of upper respiratory tract collapse. Orthodontic treatment should thus be considered as an alternative treatment for OSA children with craniofacial anomalies, however the most important aspect of therapy is an interdisciplinary approach.